Out-Of-Network Spending Mostly Declined In Privately Insured Populations With A Few Notable Exceptions From 2008 To 2016 - Song, Zirui (Health Aff (Millwood), 2020)
While out-of-network or potential “surprise” billing has garnered increasing attention, particularly in emergency department and inpatient settings, few national studies have examined out-of-network care overall or in other settings. We examined out-of-network spending and use among two large nationwide populations with employer-sponsored insurance. In a primary sample of 27,883,040 people in data for 2008–16 from the Truven MarketScan Commercial Claims and Encounters Database, we found that the unadjusted share of total spending that occurred out of network decreased from 7.0 percent in 2008–10 to 6.1 percent in 2014–16, an adjusted average decline of 0.10 percentage points per year. Using a secondary sample of 13,093,209 people in the Health Care Cost Institute database provided qualitatively similar results, including when provider charges (upper bound for balance billing) were used in place of observed out-of-network prices. In subgroup analyses of the primary sample, the share of out-of-network spending was stable or declined among all segments of care except hospitalist services, pathologist services, and laboratory tests across the study period. Out-of-network use demonstrated comparable patterns. Prices were higher out of network than in network. Policy makers should focus their efforts on protecting consumers from balance billing or potential surprise billing in clinical scenarios where patients often have little choice over their provider.